The Correlation between Leadership, Motivation, Work Climate and High Economic Teachers’ Performance in Karanganyar Regency - Siwi, Marheni Dharyadi; Siswandari, Siswandari; Gunarhadi, Gunarhadi (International Journal of Active Learning, 2019)
This research aims to find out and to analyze the correlation between leadership of the priciple, motivation and work climate with the performance of high school economics teachers in Karanganyar Regency either partially or simultaneously. This research was conducted on the high school economics teachers in Karanganyar Regency. The population of this research is all of high school economics teachers in Karanganyar Regency as much as 38 teachers and also become sample research. Analysis methods used in this research is double linear regression method. The results showed that leadership significantly to the performance of economics teachers on coefficient 0,322 and sig = 0,037. It means that the leaders’ role creates the better economics teachers’ performance. Motivation related significantly to the teachers’ performance on coefficient 0,403 and sig = 0,025. This means that good motivation influence of the teachers’ performance well. Work climate related significantly to the economics teachers’ performance on coefficient 0,452 and  sig = 0,30. Furthermore, the better work climate affects the economics teachers’ performance will be better.